BIMWIN SEBAGAI STRATEGI KOMUNIKASI BIMAS ISLAM KABUPATEN PONOROGO DALAM MENCEGAH PERCERAIAN - Mohammad Luthfi; M. Rifa’i (Jurnal Komunikasi, 2018)
ABSTRACTThis study aims to find out BIMWIN as a communication strategy for the Islamic Community Guidance in Ponorogo Regency in preventing divorce. The location of this study was located in the Islamic Guidance Office of Ponorogo Regency with the research subjects being the Head of the Islamic Guidance Section in Ponorogo Regency, the chief executive of BIMWIN, the facilitator and BIMWIN participants. The method used in this research is a qualitative descriptive approach with data collection methods through interviews, observation and documentation. The results showed that in an effort to prevent divorce, the Islamic Community Guidance in Ponorogo Regency carried out Marriage Guidance activities for prospective bridal partners. The mapping of communicants is based on the sociological and psychological aspects of the participants. The message delivery strategy is packaged in the form of lectures and group discussions that focus on participants. The media used are LCD projectors, white boards and the Sakinah Family Foundation book. The strategy of selecting communicators is based on aspects of credibility and attractiveness so that those who are used as communicators in the implementation of BIMWIN are facilitators who have been certified in the field of motivators and sakinah family counselors.